Utilization of Operating Room in Buleleng Regency Hospital based on Utilization Theory in 2020 - I Ketut Setia Budi (Journal for Quality in Public Health, 2020)
Each hospital has an operating room as a central surgical service unit. In this case it should be noted that the central surgical service unit has a different contribution from the inpatient room so it is necessary to maintain the use of this operating room in hospital services. The research objective was to determine the Utilization of Operating Rooms in Buleleng Regency Hospital based on Utilization Theory. This research method is observational analytic with crossectional design. The study population was patients who received services at IRD and CSI with a sample of 106 respondents taken by purposive sampling with criteria. The results of this study are predisposing, enabling and need factors where predisposing factors have a dominant influence on the patient's decision to use the operating room with a p-value of 0,000 showing <of α 0.05 which indicates an influence. The conclusion of this research is that there is a relationship between Predispoding variable and Enabling Facto variable on the utilization of operating room based on ultilization theory, the result of p-value shows <of α 0.05, which shows that there is an influence. And there is no relationship between variable Need Factor to operating room utilization results p-value results>> α 0.05 which shows no influence. So it is suggested that the Use of Operating Rooms in Buleleng Regency Hospital is based on Utilization Theory and applies to other rooms